Managing Students' Excessive Activity Through Gamified Learning to Improve Concentration - Lilis Rahmawati; Moh Dimas Yusuf Arifin; Devita Anggraeni (Kartika: Jurnal Studi Keislaman, 2025)
This study addresses the challenge of managing students' excessive activity and limited attention span in an elementary classroom, particularly in Grade 4A2 at MIN 4 Nganjuk. Hyperactive tendencies, characterized by high motor activity, impulsivity, and difficulty sustaining attention, often disrupt the learning process when not properly directed. Positioned within innovative pedagogical approaches, this research explores gamification as a strategic intervention to channel students' energy into constructive engagement. This study aims to describe the implementation of gamified learning and to examine its impact on students' focus and concentration. Using a qualitative approach, data were collected through classroom observation, interviews, and documentation during a four-week implementation procedure. Points, missions, badges, leaderboards, and instant feedback were integrated into daily learning activities. The findings indicate a notable improvement in students' attention span, increasing from an average of 10-15 minutes to 30-40 minutes during learning sessions. Classroom dynamics also shifted from disruptive behavior to active and collaborative participation. The study concludes that gamification can transform excessive activity into meaningful engagement while fostering concentration, positive social interaction, and emerging intrinsic motivation among students